A Case of Acute Myeloid Leukemia Mimicking Blastic Plasmacytoid Dendritic Cell Neoplasm: Utility of the Proposed Upcoming WHO-5 Diagnostic Criteria - Jhajj, Bhvaneet; Henrie, Ryan; El-Khalidy, Youness; Moshref Razavi, Habib (Case Reports in Hematology, 2023)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is an aggressive hematologic malignancy which is associated with a distinctive morphologic appearance. However, the morphology is not specific, and diagnostic characterization requires integration of immunophenotypic and genetic testing. We herein report a case of a 35-year-old female patient who presented with worsening cytopenia. A bone marrow aspirate identified medium-sized blastic cells with perinuclear microvacuoles (“pearl neckless”). Occasional blasts demonstrated a “hand mirror” appearance. Tandem flow cytometry showed an atypical population of dim CD45 events with expression of CD4, CD56, CD117, CD123, and monocytic markers such as CD64. Fluorescence in situ hybridization (FISH) showed evidence of a KMT2A rearrangement with an unknown partner on chromosome 19. Expression of MPO and muramidase was present. The final diagnosis was acute monocytic leukemia (AMoL). Due to the overlapping features of acute myeloid leukemia and BPDCN, the 5th Edition of the World Health Organization (WHO) Classification of Haematolymphoid Tumours provides new criteria for the diagnosis of BPDCN. Our case highlights the utility of these criteria.